The Use of Arabic in Teaching and Learning Activities at Madrasah Aliyah Darullughah Wadda'wah, Bangil, Pasuruan - Segaf Baharun (Al-Jadwa: Jurnal Studi Islam, 2022)
Arabic is the language that opens up Islamic knowledge and is typically taught in Islamic educational institutions such as Islamic boarding schools and madrasahs. This study aims to determine the use of Arabic in teaching and learning activities at the Madrasah Aliyah Darullughah Waddah. This study used a qualitative methodology and a case study approach. The results of this study show that using language in classroom teaching and learning activities helps students memorize and use Arabic vocabulary, and improves both their listening and speaking skills. This shows that using Arabic in the classroom significantly improves students' Arabic literacy skills.